Understanding patients’ experiences of cannulation for haemodialysis, by healthcare staff - Fielding, Catherine (2024)
Haemodialysis is a life-sustaining treatment for people with end stage kidney disease. Approximately 70% of patients on haemodialysis use arteriovenous access to provide access to the circulation, which requires cannulation (insertion of two needles) thrice weekly before each haemodialysis treatment. Patients struggle to cope with regular cannulation, for some throughout their time on haemodialysis, but studies exploring patients’ experiences of this cannulation are sparse. Therefore, this thesis aims to understand patients’ experiences of cannulation for haemodialysis as performed by healthcare professionals. This is completed through three studies described below.